Pengembangan Modul Model Pembelajaran Discovery Learning pada Materi Kinetika Kimia untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Fase F Kelas XI SMA - Ike Yusrianti; Alizar; Rahadian Zainul; Riga (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a chemistry learning module based on the discovery learning model on chemical kinetics material to improve critical thinking skills of grade XI Phase F high school students. This research is a type of development research (Research and Development) that uses the Plomp development model, which consists of three stages: preliminary research, development (prototyping phase), and assessment phase. The preliminary research stage includes needs analysis and theoretical studies as the basis for compiling the module. Furthermore, in the development stage, the module was validated by five experts to assess the feasibility of content, presentation, language, and contextual aspects. The results showed that the developed module had very high validity with an average Aiken's V value of 0.96. The practicality test showed an average value of 98.50%, which is classified as very practical. The effectiveness test produced a significance value of 0.019 (< 0.05), which indicates a significant increase in learning outcomes after using the module. It can be concluded that this discovery learning module on chemical kinetics is valid, practical, and effective in improving students' critical thinking skills. This module can be an alternative contextual teaching material that encourages active and independent learning at the high school level.